Jasa Lanskap pada Pekarangan Transmigran Bali di Wilayah Lampung Timur - Muhammad Saddam Ali; Hadi Susilo Arifin; Nurhayati Nurhayati; Made Astawan (Jurnal Ilmu Lingkungan)
The transmigration home garden was one of the potential providers of landscape services, such as ecological, economic, social and cultural services. These landscape services can improve people's welfare. The Balinese transmigrant home garden in East Lampung became the research location to see the services of the home garden landscape. Ecological approaches, economic analysis, and socio-culture analysis were carried out to determine the role of the home garden in providing  landscape services. The Balinese transmigrant home garden pattern was built based on the Rwa Bhineda concept which regulates the layout of the building. The composition of pekarangan plants was analyzed using the vertical diversity, horizontal diversity, and Summed Dominance Ratio (SDR) values of the plants. In addition, it also analyzed economic services in the form of additional income and reduced costs for consumption. The results showed that several plants such as coconut, mango, banana, and flower ornamental plants had high SDR value up to 45%. These plants are used as a component of religious rites for the Balinese transmigrant community. Home garden also provided economic services, namely additional income and reduced consumption costs up to 100% per month/family. Home garden landscape services for Balinese transmigrants were proof that community welfare can be realized through sustainable use of home gardens and had implications for the achievement of transmigration goals.